Clinical evolution of sacral stress fractures: influence of additional pelvic fractures. Issue 7 (July 1993) - Peris, P; Guañabens, N; Pons, F; Herranz, R; Monegal, A; Surís, X; Muñoz-Gómez, J
Abstract : OBJECTIVES–To evaluate the clinical evolution of sacral stress fractures in relation to the scintigraphic pattern and the presence of additional pelvic fractures. METHODS–This was a retrospective study of 14 patients with sacral fractures. RESULTS–Six patients had additional pelvic fractures. Four bone scintigraphic patterns were found. The resolution of symptoms was longer in patients with associated pelvic fractures (30 weeks v three weeks). No relation was found between the bone scintigraphic pattern and the time of evolution. CONCLUSION–Associated pelvic fractures delay the resolution of symptoms in patients with sacral fractures, regardless of scintigraphic pattern.